TAIGA AS A REGIONAL IDENTITY MARKER IN THE PROSE BY A.M. BONDARENKO - Ol’ga Nikolaevna Zyryanova (Sovremennye Issledovaniâ Socialʹnyh Problem, 2017)
The aim. The article considers regional identity in the prose of the Krasnoyarsk Territory writers. The object under consideration is the stories, the novel, and the short stories by A.M. Bondarenko, devoted to the writer’s native place; the subject under consideration is the image of taiga as the most important marker of regional identity.